The social sciences in modern Japan : the Marxian and modernist traditions - Barshay, Andrew E. (Twentieth-century Japan, 2007)
An intellectual history of Japanese social science, since the 1890s, this work considers the various forms of modernity that the processes of "development" or "rationalization" have engendered and the role social scientists have played in their emergence.